Utilization of coconut water as inducing substance in the cultivation of Pleurotus ostreatus - Elfarisna Elfarisna; Iwan Saskiawan (Jurnal AGROSAINS dan TEKNOLOGI, 2019)
Cultivation of edible mushrooms has been evaluated as an effective way for increasing income of people in developing countries. Pleurotus ostreatus, well known as an oyster mushroom is the most popular edible mushroom in Indonesia. They usually is cultivated using a sawdust as a main substrate. The aim of this research is to reveal the addition of coconut water, the byproduct of traditionally coconut process as an inducing substance in P. ostreatus cultivation.  The results shown that the addition 25% (v/v) of coconut water in substrate of P. ostreatus induce the growth of mycelium. On the other hand, the addition of 50% (v/v) of coconut water affect in the day of fruit body formation become faster as well as increase the number of pileus (stalk)  and  the weight of fruit body.